12x-13-6x+4=

Simple and best practice solution for 12x-13-6x+4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-13-6x+4= equation:


Simplifying
12x + -13 + -6x + 4 = 0

Reorder the terms:
-13 + 4 + 12x + -6x = 0

Combine like terms: -13 + 4 = -9
-9 + 12x + -6x = 0

Combine like terms: 12x + -6x = 6x
-9 + 6x = 0

Solving
-9 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 6x = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 6x = 0 + 9
6x = 0 + 9

Combine like terms: 0 + 9 = 9
6x = 9

Divide each side by '6'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 9p-7=74 | | 18n*18=9 | | 4+42x=21x+16 | | 3k-11=5-k | | p=7k^2-14k+1 | | 18.7+k=32.2 | | -18nx=9 | | (-n^3-8n-6)+(-8n^3+9n)= | | 3x-7+5=-(4x+7)+17x | | 0.5r+3=6 | | 9x+2y=114 | | 0.5+3=6 | | c=4d+5 | | 4(a-11)-7(2a+1)=-2.28 | | Z+6.8=15 | | -4.8f+6.8=-8.48 | | 8=7-2(7x+2) | | 3-2x=1-3x | | x^2=10(10-x) | | 10-1.4x=10.84 | | 25=r-3 | | -16+2x=-32+12x | | 26+9n=264 | | x^2=100-10x | | 5(4+x)=6+3x | | 7(2-3a)=3(5a-1) | | x(3x+2)=1496 | | 3x+2y=12fory | | t^2+2t-14=0 | | 3x+8=-70-10 | | -2.8(x+4.9)=8.2 | | 8s^2-6s=2s |

Equations solver categories